2019
DOI: 10.22606/pra.2019.14001
|View full text |Cite
|
Sign up to set email alerts
|

Online Dating: Is Hooking Up the Goal?

Abstract: This study examines how gender interplays with emerging adults' intentions and outcomes when using online dating. Symbolic interaction and evolutionary theories are used to understand how evolutionary symbols are associated with online dating, impacting intentions and outcomes. Utilizing a sample of 229 emerging adults, between 18-30 years of age, regression analyses show online dating intentions and outcomes associated with online dating (e.g., whether it was a casual or sexual relationship or if their desire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Although sex and emotion are not always connected (Birnbaum & Reis, 2019), this reflects females' willingness to invest emotions in love, even in STRR. Women tend to prioritize serious relationships while dating (Almond et al, 2019;Foster, 2021;Gray et al, 2019), are less likely to agree that"sex without love is acceptable" (Buss, 2018), and cite love and commitment as motives for sex more than men (Meston et al, 2020). This research and past findings on sex being viewed as an expression of love (Fazli Khalaf et al, 2018) suggest Malaysian young women are similar.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Although sex and emotion are not always connected (Birnbaum & Reis, 2019), this reflects females' willingness to invest emotions in love, even in STRR. Women tend to prioritize serious relationships while dating (Almond et al, 2019;Foster, 2021;Gray et al, 2019), are less likely to agree that"sex without love is acceptable" (Buss, 2018), and cite love and commitment as motives for sex more than men (Meston et al, 2020). This research and past findings on sex being viewed as an expression of love (Fazli Khalaf et al, 2018) suggest Malaysian young women are similar.…”
Section: Discussionmentioning
confidence: 61%
“…This result is consistent withSchwarz et al's ( 2020) finding that sex is an important component of STRR while contradicting social representation research from Brazil where sex is not part of the central core elements(Andrade & Wachelke, 2011). While previous studies have shown that males tend to view sex as key to romantic relationships(Almond et al, 2019;Thompson & O'Sullivan, 2012), that females do too is surprising. This is significant because sex is traditionally considered a taboo topic and females often viewed as more conservative in their attitudes towards toward it(Rahman et al, 2015;Thompson & O'Sullivan, 2012).…”
mentioning
confidence: 87%